Algoritma Adaptif Sistem Downlink Menggunakan Recursive Least Square (RLS) - Agus Basukesti; Bangga Dirgantara (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2017)
GPS (Global Positioning System) is the popular system for navigation which assistance 32 satellites orbiting the earth. Currently, tracking positions using the Global Positioning System (GPS) is one of the best positioning tracking methods. However, GPS has a lot o f noise, so filters are needed to handle with noise on GPS. In this research, the simulation is done to extract data from GPS sensors using RLS algorithm. From the results o f identification and simulation, it can be concluded that the algorithm works well and need to analyze the advantages and disadvantages to be implemented on the downlink system designed. From the simulation results obtained that error estimation is convergent that is the longer the smaller.